2016
DOI: 10.3171/2015.6.jns15969
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for worsened muscle strength after the surgical treatment of arteriovenous malformations of the eloquent motor area

Abstract: abbreviatioNs AUC = area under the ROC curve; AVM = arteriovenous malformation; BOLD = blood oxygen level-dependent; CST = corticospinal tract; DSA = digital subtraction angiography; DTI = diffusion tensor imaging; DW = diffusion weighted; EPI = echo-planar imaging; FA = fractional anisotropy; FAPA = feeding artery from perforating artery; fMRI = functional MRI; LAD = lesion-to-activation area distance; LCD = lesion-to-CST distance; MS = preoperative muscle strength; MS 1 = muscle strength 1 week postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Axial time-of-flight (TOF) MR angiography was performed using a 3D TOF gradient-echo acquisition sequence (TR 22 msec, TE 3.86 msec, slice thickness 1 mm, slices 36 × 4, FOV 220 × 220 mm 2 , flip angle 120°, matrix 512 × 512). 17…”
Section: Neuroimagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Axial time-of-flight (TOF) MR angiography was performed using a 3D TOF gradient-echo acquisition sequence (TR 22 msec, TE 3.86 msec, slice thickness 1 mm, slices 36 × 4, FOV 220 × 220 mm 2 , flip angle 120°, matrix 512 × 512). 17…”
Section: Neuroimagingmentioning
confidence: 99%
“…8,16 In previous studies, we demonstrated that the LED measured using fMRI and DTI data was a significant predictor of surgical outcomes for BAVM located in eloquent motor area or the occipital lobe. 17,23 However, as far as we know, there are still no prediction models for surgical outcomes of BAVM that include the LED. Whether adding LED information to a previous grading system can be used to build a supplementary grading system that would better predict neurological outcome remains unclear.…”
mentioning
confidence: 99%
“…In addition, the eloquence includes functional cortex, deep brain, and brain stem, while some important subcortical tracts are outside the scope of the definition. Compared with the cortex, tract injury seems to result in a more long-term neurological deficit, where the functional reorganization might be slow [24]. …”
Section: Discussionmentioning
confidence: 99%
“…However, there was still no significant association between fMRI navigation and the incidence of S-PFD in the patient subgroups, such as patients with eloquent-area AVMs (p = 0.891) or with low preoperative mRS score (0-1) (p = 0.753). In our previous studies, 18 we have determined that preoperative functional findings derived from BOLD-fMRI and DTI are predictive of surgical outcomes in patients with AVMs. The use of DTI tractography allows assessment of important white matter tracts, and BOLD-fMRI enables functional mapping of at-risk cortex in the vicinity of an AVM.…”
Section: Figmentioning
confidence: 99%